Critical Management of Haemodynamically Unstable Acute Pulmonary Embolism in COVID-19 - Eka Adip Pradipta; Vienna Rossimarina; Indira Kemalasari; Siska Suridanda Danny (Acta Medica Indonesiana)
Increased thrombotic events that occur in up to one-third of patients with COVID-19 are predominantly pulmonary emboli (PE), which are associated with higher severity and increased mortality. Acute PE should therefore be one of the main differential diagnoses among patients with hemodynamic instability. Early treatment of such a condition with systemic thrombolysis remains the first line of treatment especially in patients with COVID-19, which hinders further invasive intervention. The aim of this report is to describe a typical case of hemodynamically unstable acute PE with COVID-19 management in our center to emphasize the role of early detection and prompt treatment of such a condition. A 66-year-old male suspected of having COVID-19 initially presented with shortness of breath and desaturation with normal physical examination, and turned out to be COVID-19 positive. In the isolation ward, he had a cardiac arrest, and bedside echocardiography showed a fresh thrombus had developed in the right atria with signs of acute right ventricular dysfunction. The diagnosis of acute PE with hemodynamic instability was established, and systemic thrombolysis was immediately initiated. The patient recovered well with improvement in his symptoms and was eventually safely discharged. Our case demonstrates how early recognition and prompt treatment of acute PE especially in COVID-19 patients with hemodynamic instability is a life-saving intervention. Identifying the subtle clues of acute PE in emergency situations remains the main challenge.